The tadpole of Rhinella crucifer (WIED-NEUWIED, 1821) (Amphibia: Anura: Bufonidae) from southern Bahia, Brazil - Ruas, Danilo Silva; de Mira Mendes, Caio Vinicius; Szpeiter, Bruno Bernal; Solé, Mirco (Zootaxa, 2012)
According to Baldissera et al. (2004) the Rhinella crucifer group includes five recognized species: Rhinella crucifer (Wied-Neuwied, 1821); R. ornata (Spix, 1824); R. henseli (A. Lutz, 1924); R. abei and R. pombali (Baldissera, Caramaschi & Haddad, 2004). The distribution of this group is associated to the Atlantic Rain Forest, from Ceará to Rio Grande do Sul, adjacent areas in Minas Gerais and São Paulo, Brazil. One species also occurs in Uruguay and northeastern Argentina, in the Misiones and Corrientes provinces (Baldissera et al. 2004; Frost 2011). Thomé et al. (2010) in a phylogeographic study of the Rhinella crucifer group identified two subclades in northeastern Brazil and adjacent areas: one ranging from Bahia to Paraíba and another from Minas Gerais to Espírito Santo. Of five species belonging to the R. crucifer group, only two have described tadpoles, R. ornata and R. pombali (Heyer et al. 1990, where the tadpole described as R. crucifer represents R. ornata; Lourenço et al. 2010). Here we described the tadpole of R. crucifer from a population from southern Bahia.